Violation of traffic safety when using chloride dir in railway transport - Popov Vladimir; Churiukina Svetlana; Sukhov Philipp; Borovkov Yuri; Balandova Julia (E3S Web of Conferences, 2019)
This article experimentally proves the negative (destructive) effect of chloride DIR on railway transport facilities. The ways of chloride DIR getting of various objects of railway transport are shown. The relationship between the usage of chloride DIR and the violation of traffic safety in railway transport is being proven. Possible scenarios of the occurrence of a violation of traffic safety without taking into account the occurrence of human casualties are presented.